Sidney Poitier : man, actor, icon - Goudsouzian, Aram (The University of North Carolina Press, 2004)
Aram Goudsouzian analyzes the life and career of Hollywood legend Sidney Poitier, from his childhood in the Bahamas to his 2002 Oscar for lifetime achievement. Poitier is a gifted actor, a great American success story, an intriguing personality, and a political symbol; his life and career tell much about race relations since the 1960s.